Raspberry marc extracts increase antioxidative potential, ellagic acid, ellagitannin and anthocyanin concentrations in fruit purees. (March 2016) - Bobinaitė, Ramunė; Viskelis, Pranas; Bobinas, Česlovas; Mieželienė, Aldona; Alenčikienė, Gitana; Venskutonis, Petras Rimantas
Abstract: Two types of fruit puree consisting of (1) pears/apples/yellow cherry plums and (2) apples/black currants were enriched with raspberry marc extract containing valuable antioxidants. The addition of 2% marc extract increased total phenolic content (TPC) from 108.8 to 345.8 and from 176.1 to 396.2 mg/100 g in the puree (1) and (2), respectively. The total anthocyanin content (TAC), ellagic acid and ellagitannin concentrations as well as antioxidant capacity of purees also increased with increasing concentration of marc extract additive. The increase of free ellagic acid (up to 44%) in the purees with extract additives after preparation was related to a partial hydrolysis of ellagitannins. Higher extract concentrations resulted in the increased bitterness and astringency of the products; therefore the concentration of raspberry marc additives in purees of up to 1.6% may be recommended. Highlights: Raspberry marc extract – a rich source of polyphenolic antioxidants, ellagitannins. Its additives up to 2% remarkably increased antioxidant potential of fruit purees. Its additives remarkably enriched fruit purees with ellagitannins & anthocyanins. Its additives up to 1.6% were acceptable in terms of sensory quality of fruit purees. Raspberry marc extract ingredients increase nutritional value of fruit purees.